2014
DOI: 10.1007/s12031-014-0470-9
|View full text |Cite
|
Sign up to set email alerts
|

Novel Interactive Partners of Neuroligin 3: New Aspects for Pathogenesis of Autism

Abstract: Autism is a neurodevelopmental disorder with a strong genetic predisposition. Neurolign 3 (NLGN3) as a postsynaptic transmembrane protein, functions in both neuron synaptogenesis and glia-neuron communications. Previously, a gain of function mutation (R451C) in NLGN3 was identified in autistic patients, which illustrates the involvement of NLGN3 in autism pathogenesis. As proper synaptic targeting and functioning are controlled by intracellular protein interactions, in the current study, we tried to discover t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Two independent screens identified many proteins that interact with NLGN2 and NLGN3 c-tails, and these interactions have yet to be characterized [44,54]. Moreover, a critical region was identified in the C-terminal regions of NLGN1 and NLGN3 that is required for these molecules to potentiate excitatory synaptic transmission [24] without a known direct binding partner (Figure 3).…”
Section: Nlgn3 E a S P P H D T -L R L T A L P D Y T L T L R R S P D Dmentioning
confidence: 99%
“…Two independent screens identified many proteins that interact with NLGN2 and NLGN3 c-tails, and these interactions have yet to be characterized [44,54]. Moreover, a critical region was identified in the C-terminal regions of NLGN1 and NLGN3 that is required for these molecules to potentiate excitatory synaptic transmission [24] without a known direct binding partner (Figure 3).…”
Section: Nlgn3 E a S P P H D T -L R L T A L P D Y T L T L R R S P D Dmentioning
confidence: 99%
“…The protein encoded by ITPRIP binds to the inositol-1,4,5-triphosphate receptor (IP 3 R) and allosterically downregulates IP 3 -induced calcium release from the endoplasmic reticulum [54]. Oligomeric aβ 42 alters IP 3 -triggered calcium release [55] and, in return, IP 3 -induced calcium release may influence amyloid precursor protein (APP) cleavage to aβ 40 and aβ 42 [56].…”
Section: Discussionmentioning
confidence: 99%
“…Oligomeric aβ 42 alters IP 3 -triggered calcium release [55] and, in return, IP 3 -induced calcium release may influence amyloid precursor protein (APP) cleavage to aβ 40 and aβ 42 [56]. Thus, ITPRIP may interact with IP 3 R to modulate both the aβ concentration and synaptic plasticity through calcium signaling [54]. A pathway analysis of plasma aβ GWAS results lent credibility to our ITPRIP finding [12]; eighteen of twenty-seven Ingenuity canonical pathways associated with plasma aβ contained the receptor (IP 3 R) modulated by ITPRIP.…”
Section: Discussionmentioning
confidence: 99%
“…Filamin is present in acetylcholine receptor clusters at the mammalian NMJ (Bloch and Hall, 1983; Shadiack and Nitkin, 1991), but its function there is unknown. In lysates of the mammalian brain, filamin associates with known synaptic proteins such as Shank3, Neuroligin 3, and Kv4.2 (Petrecca et al, 2000; Sakai et al, 2011; Shen et al, 2015). A recent report indicated that filamin degradation promotes a transition from immature filopodia to mature dendritic spines (Segura et al, 2016), a phenomenon that is likely to be related to the actin-bundling properties of the long isoform of filamin.…”
Section: Discussionmentioning
confidence: 99%